0730 Individuals Receiving Methadone For Medication-Assisted Treatment Of Opioid Use Disorder Show Evidence Of Respiratory Depression. (27th May 2020) - Finlay, M; Wilson, M; Erwin, J A; Hansen, D A; Layton, M E; Quock, R M; Van Dongen, H
Abstract: Introduction: A well-established consequence of opiate use is respiratory depression during sleep, with a high prevalence of central sleep apneas. Medication-assisted treatment (MAT) is a widely used therapy for opioid use disorder (OUD) designed to reduce withdrawal symptoms and drug cravings. We investigated the presence of respiratory depression during sleep in patients receiving methadone-based opioid replacement treatment as part of a MAT program for OUD. Methods: N=6 individuals (5 females, ages 43.8±12.8y, BMI 27.2±4.1kg/m 2 ), who were within 90 days of methadone initiation, underwent in-laboratory overnight polysomnography (8h TIB, 22:00-06:00). Apneaic and hypopneic events were determined using AASM criteria. Results: The average Apnea-Hypopnea Index (AHI) was 16.5±9.0 events/h, with 2 individuals exceeding the threshold of moderate sleep apnea (>15 events/h). 89.5% of the observed apnea-hypopnea events occurred during NREM sleep. Of all events, 57.1±16.3% were central apneas; and of all obstructive, central, and mixed apnea events, 93.0±14.3% were central apneas. Conclusion: Individuals with OUD receiving methadone-based MAT may be at risk of respiratory depression during sleep, as evidenced by the frequent occurrence of central sleep apneas. Such risk could be a contributing factor in opioid overdose deaths. Currently, performing respiratory assessments during sleep is not considered standard of care in MAT programs. Our preliminary data suggest that monitoring and treatment of respiratory depression during sleep may be indicated in OUD patients on methadone-based MAT. Support: Supported in part by a seed grant from the Washington State University Office of Research Advancement and Partnerships.